2013
DOI: 10.1111/cxo.12025
|View full text |Cite
|
Sign up to set email alerts
|

A new perspective on the pathobiology of keratoconus: interplay of stromal wound healing and reactive species‐associated processes

Abstract: Severe loss of vision manifests from the corneal protrusion, thinning and distortion that characterises keratoconus, which in its most severe form is still treated primarily by lamellar or penetrating keratoplasty. Unfortunately, alternative therapeutic options targeting the underlying pathobiology remain limited, attributable to an incomplete understanding of the biological mechanisms instigating stromal deterioration and other disease processes. We postulate that underlying abnormalities in stromal repair an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 139 publications
3
45
0
Order By: Relevance
“…84 There is also a report of an increase in type IX collagen and a dysregulation in type XVIII collagen expression posterior to the healing process in patients with keratoconus. 85 Cheung et al, 74,86 analyzing ex vivo the modulation of the healing process of corneas with keratoconus and of non-keratoconic corneas, found that fibroblast growth factor 2 (FGF-2), platelet-derived growth factor (PDGF), and epidermal growth factor (EGF) were found to be upregulated in keratoconic corneas in comparison with normal uninjured corneas, but following an ex vivo secondary injury EGF, FGF-2, and PDGF were found to be downregulated in both non-keratoconic and keratoconic corneas, but they were decreased further in the later ones (FGF-2 was reduced to undetectable levels). According to those results, the authors concluded that dysregulation of reparative pathways in keratoconus causes on the one hand keratoconic corneas to appear in a perpetually injured state, but on the other hand they also produce a weakened repair response to a secondary lesion (eg, eye rubbing or contact lens wear and oxidative damage), which further supported what the authors had previously postulated: that underlying abnormalities in stromal repair and activities linked to oxygen reactive species along with the interaction between these phenomena were implicated in the development of keratoconus.…”
Section: Corneal Stroma Compositionmentioning
confidence: 98%
See 4 more Smart Citations
“…84 There is also a report of an increase in type IX collagen and a dysregulation in type XVIII collagen expression posterior to the healing process in patients with keratoconus. 85 Cheung et al, 74,86 analyzing ex vivo the modulation of the healing process of corneas with keratoconus and of non-keratoconic corneas, found that fibroblast growth factor 2 (FGF-2), platelet-derived growth factor (PDGF), and epidermal growth factor (EGF) were found to be upregulated in keratoconic corneas in comparison with normal uninjured corneas, but following an ex vivo secondary injury EGF, FGF-2, and PDGF were found to be downregulated in both non-keratoconic and keratoconic corneas, but they were decreased further in the later ones (FGF-2 was reduced to undetectable levels). According to those results, the authors concluded that dysregulation of reparative pathways in keratoconus causes on the one hand keratoconic corneas to appear in a perpetually injured state, but on the other hand they also produce a weakened repair response to a secondary lesion (eg, eye rubbing or contact lens wear and oxidative damage), which further supported what the authors had previously postulated: that underlying abnormalities in stromal repair and activities linked to oxygen reactive species along with the interaction between these phenomena were implicated in the development of keratoconus.…”
Section: Corneal Stroma Compositionmentioning
confidence: 98%
“…Recent technological advances have enabled more sophisticated molecular studies of the keratoconic condition, which changed some of the previously conceived theories for its pathogenesis. 3,24,25,[73][74][75][76] Pathophysiologic components of keratoconus can be largely classified into the following: alterations of the stroma composition, imbalance of pro-inflammatory and anti-inflammatory molecules, imbalance of the enzymes that cause extracellular matrix degradation and their corresponding inhibitors, oxidative stress, and cellular hypersensitivity. These events occur simultaneously and may present positive feedback between one another.…”
Section: Pathophysiologymentioning
confidence: 99%
See 3 more Smart Citations